Ketahanan Jamur terhadap Fungisida di Indonesia - Christanti Sumardiyono (Jurnal Perlindungan Tanaman Indonesia, 2008)
Plant diseases control with fungicides had been practised for decades in Indonesia. The orientation of consumers to have high quality agriculture product caused the intensif use of pesticides including fungicides. Systemic fungicides were used as therapeutant agens for disease control. Intensively used and sublethal dose of systemic fungicides induced fungi to be resistant. The purpose of this article was to describe the occurrence of developing fungicides resistance strains. Several publications reported that there were some fungicides which induced resistant strain i. e. benomyl and its metabolites, metalaxyl and simoksanyl. It was assumed that the resistant strain occurred due to the genetic of pathogens, mode of action of fungicides and method of application. Resistance to contact or nonsystemic fungicides was rare compared with systemic one. The single site action of systemic fungicides caused mutation of fungus to be resistant. This fenomena did not occure against contact fungicides with multisite actions. Among systemic fungicides, benomyl resistant strains were more frequently reported than the others. To avoid those problems the authors strongly suggested to use Integrated Pest Management in plant disease control. Reduced frequency of fungicides applications, using recommended dose and mixture of contact and systemic fungicides are several tactics to delay resistance. Risk assessment and monitoring of fungicides resistance at molecular level is also suggested.